Analisis Inovasi Aplikasi Identitas Kependudukan Digital dalam Meningkatkan Pelayanan Publik oleh Dinas Kependudukan dan Pencatatan Sipil di Kelurahan Kebon Bawang, Jakarta Utara - Anisa Darajatun; Ana Chaerunisyah (Jurnal Ilmu Administrasi Publik, 2025)
e-Government and the electronic identity card (e-KTP) are tangible examples of technological advancement in the public sector, including the implementation of the Digital Population Identity (IKD), a digital system that integrates population data to streamline information management and support the provision of administrative services to community. However, as of now, 67.38% or 29,526 out of 43,816 residents of Kebon Bawang Sub district have yet to activate the system, primarily due to various technical and socialization- related constraints. This research aims to examine the effectiveness of the IKD application innovation in Kebon Bawang Sub district and to identify the barriers as well as efforts to overcome them. The research method employed is qualitative descriptive, with data collected through interviews, observations, and documentation. The findings reveal that although the IKD application offers benefits in terms of access and time efficiency, public services in the field remain largely manual due to the low activation rate and suboptimal application performance. Therefore, through outreach programs such as “Jemput Bola” (Proactive IKD Registration Initiative), community participation in IKD activation is expected to significantly enhance awareness and understanding of the digital transformation of population administrative services.